Impact of Auditor Independence on Audit Quality of Listed Insurance Companies in Nigeria - Timothy Aondona Aondover (Britain International for Academic Research (BIAR-Publisher), 2025)
In recent times, Nigeria has battled towards breaking loose from the recent excruciating economic recession; the need to maintain investors’ confidence in the capital market through high-quality audit and transparent financial reporting is unequivocally paramount. Within this context, the study examines the impact of auditor independence on audit quality of listed insurance companies in Nigeria. The study espoused on Auditors’ Theory of Inspired Confidence, as a theoretical background to develop an empirical framework to examined auditor independence and audit quality of listed insurance companies in Nigeria. Ex-post facto research design was adopted as well as the existing financial statement of listed insurance companies in Nigeria using secondary data. The population of this study comprised of all the 26 insurance companies listed in the Nigerian Stock Exchange (NSE) at 31st December, 2020 while 10 listed insurance companies constitute the sample size of the study. Spearman correlation coefficient was used in other to determine the relationship between audit quality and audit independence. Based on the findings, the study discovered that audit fee has significant impact on audit quality of listed insurance companies in Nigeria. Audit tenure has no significant impact on audit quality of listed insurance companies in Nigeria and audit rotation has significant impact on audit quality of listed insurance companies in Nigeria. The study concludes that audit quality was found to be significantly related to audit fee with a positive relationship. The positive relationship implies that the quality of audit dependent on the audit fee. The higher the audit fee, the higher qualitative and reliable the audit work will be. The study recommends that government through the various professional bodies should develop robust policies that will help improve audit quality in Nigeria through effective audit rotation so as to avoid familiarity.